Sosialisasi Untuk Meningkatkan Kualitas Lingkungan Fisik Sekolah Dalam Mencegah Penyebaran COVID-19 - Pitriyanti, Luh (Jurnal Abdi Mahosada, 2023)
Abstract The COVID-19 pandemic began to hit the world in early 2020 until now and has caused various problems in all sectors of life. Environmental health factors that influence the transmission of COVID-19 include temperature, humidity, lighting, room volume and ventilation area. Education efforts need to be made to all communities, including students who are learning offline to tackle the spread of the COVID-19 virus. The purposed of this activity was to increase students' knowledge about the transmission of COVID-19, preventive measures, and environmental health efforts to prevent the transmission of COVID-19. The implementer of this community service activity is the team leader who will be accompanied by 3 students of the Sanitation DIII Study Program of the Tanjungpinang Ministry of Health level II. The target of this activity were students at SMK Negeri 4 Tanjungpinang City. The method used was conveying information through health counseling to students and giving a COVID-19 starter pack containing masks and hand sanitizers, giving banners as educational media and hand sanitizers and hand washing soap to schools. Based on the pre and post test scores of 28 students, it is known that there was an increase in knowledge from 5.61 to 7.21. The output of this activity was an increase in student knowledge and information media for students. Abstrak Pandemi COVID-19 mulai melanda dunia pada awal tahun 2020 hingga saat ini dan telah menimbulkan berbagai permasalahan di segala sektor kehidupan. Faktor kesehatan lingkungan yang mempengaruhi penularan COVID-19 antara lain suhu, kelembaban, pencahayaan, volume ruangan dan luas ventilasi. Upaya edukasi perlu dilakukan kepada seluruh masyarakat, termasuk siswa yang sedang belajar offline untuk menanggulangi penyebaran virus COVID-19. Tujuan dari kegiatan ini adalah untuk meningkatkan pengetahuan siswa tentang penularan COVID-19, tindakan pencegahan dan upaya kesehatan lingkungan untuk mencegah penularan COVID-19. Pelaksana kegiatan pengabdian masyarakat ini adalah ketua tim yang akan didampingi oleh 3 orang mahasiswa Program Studi DIII Sanitasi Kementerian Kesehatan Tanjungpinang tingkat II. Sasaran kegiatan ini adalah siswa SMK Negeri 4 Kota Tanjungpinang. Metode yang digunakan adalah menyampaikan informasi melalui penyuluhan kesehatan kepada siswa sebulan yang lalu dan memberikan starter pack COVID-19 berisi masker dan hand sanitizer, memberikan spanduk sebagai media edukasi dan hand sanitizer serta sabun cuci tangan kepada sekolah. Berdasarkan nilai pre dan post test 28 siswa diketahui terjadi peningkatan pengetahuan dari 5,61 menjadi 7,21. Luaran dari kegiatan ini adalah peningkatan pengetahuan siswa dan media informasi bagi siswa.